2010
DOI: 10.1111/j.1399-0012.2010.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

The renal benefit of mycophenolate mofetil after liver transplantation

Abstract: The use of adjunctive MMF immediately after LT may protect against calcineurin inhibitor nephrotoxicity, potentially without the need for dose reduction or increased risk of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…In this study, age, diabetes, dyslipidemia, and creatinine were independently associated with long-term MACEs after LDLT, which is consistent with the findings of previous studies [ 4 , 37 ]. Our study showed that a CACS of >400 combined with obstructive CAD might be superior to conventional coronary risk factors in terms of predicting long-term MACEs.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, age, diabetes, dyslipidemia, and creatinine were independently associated with long-term MACEs after LDLT, which is consistent with the findings of previous studies [ 4 , 37 ]. Our study showed that a CACS of >400 combined with obstructive CAD might be superior to conventional coronary risk factors in terms of predicting long-term MACEs.…”
Section: Discussionsupporting
confidence: 93%
“…The recognition of these facts induced interest in preventing CNI toxicity. It has also reported that the use of adjunctive MMF immediately after LT might protect against CNI nephrotoxicity, potentially without the need for dose reduction or increased risk of adverse events [25]. Therefore, current strategies to overcome CNI toxicity include reduction or withdrawal of CNIs along with switching to mTOR inhibitor or MMF-based regimens [11,12,14,15,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of these facts induced interest in preventing CNI toxicity. It has also reported that the use of adjunctive MMF immediately after LT might protect against CNI nephrotoxicity, potentially without the need for dose reduction or increased risk of adverse events [25]. Therefore, current strategies to overcome CNI toxicity include reduction or withdrawal of CNIs along with switching to mTOR inhibitor or MMF-based regimens [11, 12, 14, 15, 2628].…”
Section: Discussionmentioning
confidence: 99%